A case report of AIDS complicated by Pneumocystis jirovecii and Tropheryma whipplei mixed pulmonary infection identified via metagenomic next-generation sequencing - Sun, Xiaokui; Gong, Qiangjin (Frontiers in Medicine, 2025)
Tropheryma whipplei (TW) is a Gram-positive bacterium that is rarely encountered in clinical practice. It primarily affects the digestive and nervous systems, with pulmonary infections being infrequently reported. This case report describes a patient with HIV/AIDS who developed a mixed pulmonary infection involving Pneumocystis jirovecii pneumonia (PJP) and TW. The diagnosis was confirmed via metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid obtained through bronchoscopy. Following appropriate treatment, the patient’s symptoms and pulmonary imaging findings showed marked improvement.